1985
DOI: 10.1159/000309589
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Function in Mucolipidosis IV

Abstract: In an 18-month-old girl affected by mucolipidosis IV (ML IV) with mild corneal clouding, normal retinal activity was documented by electroretinogram (ERG) and slightly delayed optic pathway conduction was revealed by visual evoked potential (VEP). Re-examination 9 years later disclosed severe retinal alterations resulting in atrophy with reduced photopic and missing scotopic ERG components and flat VEP. These fundoscopic and electrophysiologic deteriorations in ML IV suggest progressive rod-cone impairment sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…The current study systematically investigated the clinical and natural history features of the largest cohort of patients with MLIV published to date. 34 Similar progressive retinal alteration is also seen in tapetoretinal dystrophy and in a few cases of mucopoly-saccharidoses. The disease is usually manifested by visual impairment due to corneal opacity and retinal dystrophy, psychomotor retardation consisting of delayed milestones, hypotonia that gradually progressed to spasticity, and bilateral pyramidal tract signs.…”
Section: Results Patient History and Clinical Characteristicsmentioning
confidence: 78%
“…The current study systematically investigated the clinical and natural history features of the largest cohort of patients with MLIV published to date. 34 Similar progressive retinal alteration is also seen in tapetoretinal dystrophy and in a few cases of mucopoly-saccharidoses. The disease is usually manifested by visual impairment due to corneal opacity and retinal dystrophy, psychomotor retardation consisting of delayed milestones, hypotonia that gradually progressed to spasticity, and bilateral pyramidal tract signs.…”
Section: Results Patient History and Clinical Characteristicsmentioning
confidence: 78%
“…Although there are only a few longitudinal studies of eye pathology in MLIV, they demonstrate progressive worsening of ophthalmic features in patients. 2,4,51 Data in Mcoln1 À/À mice revealed that thinning of photoreceptor layer and ERG responses were not progressive in the course of disease. Nevertheless, despite the altered time course, recapitulation of the photoreceptor and optic nerve pathological features of MLIV in Mcoln1 À/À mice makes it a good model for preclinical gene therapy testing for this devastating disease.…”
Section: Discussionmentioning
confidence: 97%
“…Even if some of the less severely affected patients do not display clear psychomotor disabilities, the ocular disturbances may still be present [31, 32]. Along with bilateral corneal opacity and optic atrophy, the retinal degeneration results in complete blindness by the end of the first decade of life [2528, 33, 34]. Patients have also been reported to exhibit other ocular disturbances including pain, strabismus, bouts of excessive tearing and conjunctivitis, and occasional photophobia [26, 35].…”
Section: Mucolipidosis Type Iv: a Clinical Perspectivementioning
confidence: 99%